2022
DOI: 10.1002/iid3.621
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immune responses to the Sinopharm/BBIBP‐CorV vaccine

Abstract: Background To determine the kinetics and persistence of immune responses following the Sinopharm/BBIBP‐CorV, we investigated immune responses in a cohort of Sri Lankan individuals. Methods SARS‐CoV‐2 specific total antibodies were measured in 20–39 years ( n = 61), 40–59 years ( n = 120) and those >60 years of age ( n = 22) by enzyme‐linked immunosorbent assay, 12 weeks after the second dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
4
24
0
2
Order By: Relevance
“…Studies on immune response induced by BBIBP-CorV have shown differing results. In Sri Lanka, more than 90% seropositivity was observed was seen that 6 weeks post-vaccination [15,17]. A study from the United Arab Emirates showed seropositivity of 78% in the general population after full vaccination [18], with a similar result shown in a report from Pakistan [19].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies on immune response induced by BBIBP-CorV have shown differing results. In Sri Lanka, more than 90% seropositivity was observed was seen that 6 weeks post-vaccination [15,17]. A study from the United Arab Emirates showed seropositivity of 78% in the general population after full vaccination [18], with a similar result shown in a report from Pakistan [19].…”
Section: Introductionmentioning
confidence: 53%
“…It is particularly important to have data from high infectious disease burden regions with limited COVID-19 vaccine access and where primarily, inactivated vaccines were administered as humoral responses against SARS-CoV-2 are driven both by natural infection and COVID-19 vaccinations [20][21][22][23]. High seropositivity rates following natural infection have been associated with high population densities and rapid transmission resulting in high rates of infection [17]. In early 2021, we observed COVID-19 antibodies to spike to be present in greater than 50% of unvaccinated healthy blood donors [24].…”
Section: Introductionmentioning
confidence: 99%
“…Neutralization titer was decreased against the Beta variant, a greater degree was found with the Delta variant. RBD binding antibodies of the serum samples were also decreased against the VOCs [58]. It was also reported that the neutralizing activity against wild-type virus was 80% after two doses of inactivated BBIBP-CorV and only 10% serum samples showed successful neutralization against the Omicron variant.…”
Section: Inactivated Vaccinesmentioning
confidence: 76%
“…Previous studies confirmed a two-dose schedule of 2 μg BBIBP-CorV on Days 0 and 21 was sufficient to provide superior protection in mice and nonhuman primates and induce high levels of seroconversion rates and neutralization antibody titers in human 40 , 50 . Moreover, BBIBP-CorV demonstrated its good protective effect against SARS-CoV-2 variants such as B.1.351 (Beta) and B.1.617.2 (Delta) 51 . Therefore, our results indicate the S663V-RBD may provide a superior protective effect against SARS-CoV-2 and its variants.…”
Section: Discussionmentioning
confidence: 99%